2010
DOI: 10.1007/s12185-010-0701-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pretreatment of allografts with methoxypolyethylene glycol-succinimidyl-propionic acid ester in combination with an anti-OX40L monoclonal antibody in relieving graft-versus-host disease in mice

Abstract: We designed to determine whether pretreatment of allografts with methoxypolyethylene glycol-succinimidyl-propionic acid ester (mPEG-SPA) and an anti-OX40L monoclonal antibody (McAb) can relieve acute graft-versus-host disease in allogeneic bone marrow transplantation recipients. Responder splenocytes from C57BL/6 donor mice were incubated with stimulator splenocytes from BALB/c recipient mice for 7 days in the presence or absence of anti-OX40L McAb followed by mPEG-SPA modification. Donor BM cells plus mixed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…In our acute GVHD models, the symptoms of the different mice appeared in more concentrated time spans, and the clinical manifestations and pathological changes of the target tissues were typical, which made them suitable for subsequent observation and follow-up studies on GVHD (Cao et al, 2010;Huang et al, 2010;Wang et al, 2012). In the present experiments, mice in the transplantation control group suffered from severe GVHD with high clinical scores.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In our acute GVHD models, the symptoms of the different mice appeared in more concentrated time spans, and the clinical manifestations and pathological changes of the target tissues were typical, which made them suitable for subsequent observation and follow-up studies on GVHD (Cao et al, 2010;Huang et al, 2010;Wang et al, 2012). In the present experiments, mice in the transplantation control group suffered from severe GVHD with high clinical scores.…”
Section: Discussionmentioning
confidence: 89%
“…Removal of T cells before transplantation and the application of immunosuppressants are the primary strategies in the prevention and treatment of GVHD, yet the former increases the incidence of graft rejection and leukemia relapse, while the latter has severe toxic side effects that often lead to lethal infections. Studies have demonstrated that an immune tolerance of the graft by the host induced by adoptive immunotherapy of mesenchymal stem cells, (Edinger et al, 2009;Huang et al, 2010;Alpdogan and van den Brink, 2012), regulatory T cells, natural killer cells, dendritic cells, etc., has shown favorable results in the prevention and treatment of GVHD (Cools et al, 2007;Joo et al, 2010;Morales-Tirado et al, 2011). Dendritic cells (DCs) comprise heterogeneous cell populations with different subsets and various functions.…”
Section: Introductionmentioning
confidence: 99%
“…Th1 cytokines function in immune activation, modulate cellular immune responses, enhance the activation and recruitment of macrophages, recruit B cells and promote cytotoxic T-cell proliferation to promote GVHD. By contrast, Th2 cytokines are associated with immunologic tolerance and reduce production of causative agents of GVHD (4,42).…”
Section: Discussionmentioning
confidence: 99%
“…Transplantation was performed 4 h following irradiation. Mice were randomly assigned to five groups (n=10 per group), excluding those used for chimera analysis and cytokine determination: i) TBI alone, infused with 0.3 ml normal saline by the caudal vein; ii) leukemia model group, infused with isogeneic 5x10 6 spleen cells, 5x10 6 bone marrow cells and 5x10 3 EL4 cells by the caudal vein; iii) allo-BMT group, infused with donor mice 5x10 6 spleen cells, 5x10 6 bone marrow cells and 5x10 3 EL4 cells by the caudal vein (data for the GVHD model were excluded because the GVHD model was common (4,20) and a GVL effect was observed); iv) pXZ9-imDC group, infused with 5x10 6 spleen cells from donor mice, 5x10 6 bone marrow cells, 5x10 3 EL4 cells and 5x10 6 pXZ9-imDCs by the caudal vein; and v) sTNFR1-imDC group, infused with donor mice 5x10 6 spleen cells, 5x10 6 bone marrow cells, 5x10 3 EL4 cells and 5x10 6 sTNFR1-imDCs by the caudal vein.…”
Section: El4 Leukemia/lymphoma Model and Groupingmentioning
confidence: 99%
See 1 more Smart Citation